Genetic counselling for handicapped school leavers. Issue 5 (October 1981) - Vowles, M
Abstract : A total of 287 school leavers with 299 unassociated handicaps from seven special schools for physically handicapped, visually handicapped, and deaf children were given genetic counselling from 1973 to 1979. The practical aspects of running this project are described. The risks needed were those of having an affected child: 54 (18.8%) were given a high risk (greater than 1 in 10), 89 (31.0%) were given a moderate risk (1 in 10 to 1 in 40), 69 (24.0%) were given a low risk (less than 1 in 40), and 83 (28.5%) were told that risk was the same as that of general population. Of the 299 total handicaps, 25 (8.4%) were thought to be autosomal dominant conditions, 38 (12.7%) to be autosomal recessive conditions, and 8 (2.7%) to be X linked conditions. Empirical risks were given for 145 (48.5%) diagnoses, and general population risks for the remaining 83 (27.7%).